VAGINOPLASTY BY USING AMNION GRAFT IN PATIENTS OF VAGINAL AGENESIS ASSOCIATED WITH MAYOR-ROKITANSKYKUSTER-HAUSER SYNDROME - Sarwar, Iram; Sultana, Ruqqia; Nisa, Rahat Un; Qayyum, Iftikhar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Vaginal agenesis is congenital anomaly of the female genital tract and may occur as isolated developmental defect or as part of a complex of anomalies. The aim of this study was to determine the effectiveness of vaginoplasty by using amnion as graft in the creation of neovagina for patients with Mayor-Rokitansky-Kuster-Hauser Syndrome. Methods: this is a retrospective study of 28 cases of vaginal agenesis associated with Mayor-Rokitansky-Kuster-Hauser Syndrome, over the period of 20 years, in which vaginoplasty was done by modified McIndoe procedure by using amnion as graft. Results: vaginoplasty using amnion graft was successfully performed in all except one case in which rectum got opened and procedure was abandoned after the repair of rectum. The functional results were quite satisfactory. Except one case none had any significant peri-operative complication. Post surgical results were acceptable to the patients sexually and aesthetically. Conclusion: Although new techniques of vaginoplasty have evolved over the years using laparoscopic approach and by use of different materials as graft, vaginoplasty with amnion graft is still a safe and effective procedure to treat patients of vaginal agenesis. The technique is simple and safe and provides a satisfactory and functional vagina in majority of the patients. Keywords: vaginoplasty, amnion graft, vaginal agenesis, vaginal atresia, Mayor-RokitanskyKuster-Hauser Syndrome